ECMO: a lifesaving modality in ARDS during puerperium - Juneja, Sunil K.; Tandon, Pooja; Gupta, Vivek; Wander, Gurpreet S.; Mahajan, Rajesh; Singh, Akashdeep; Aggarwal, Reetika; Narang, Monika; Raina, Suhasini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Acute respiratory distress syndrome (ARDS) is an uncommon condition encountered in pregnancy. The incidence of ARDS in pregnancy has been reported to be 1 in 6229 deliveries with mortality rates to range from 24% to 39% in pregnant patients. An essential component in management of ARDS involves good communication between the obstetrics team and critical care specialist and a fundamental understanding of mechanical ventilatory support. In critically ill patients where both cardiorespiratory support is required, Extracorporeal Membrane Oxygenation (ECMO) can be used to help maintain the vital functions. ECMO is a temporary cardio respiratory or respiratory support in critically ill patients who are unresponsive to conventional management. In present case a young female with post-partum ARDS was successfully managed with extra corporeal membrane oxygenation (ECMO).